Mathematical foundations of computer science 1997 proceedings - Privara Igor ed.; International Symposium, MFCS '97 on Mathematical Foundations of Computer Science (22nd : 25-29 Aug 1997 : Bratislava,Slovakia); International symposium, MFCS '97 on mathematical foundations of computer science Bratislava, Slovakia 25-29 Aug 1997 (Berlin Springer-Verlag, 1997)
The 40 revised full papers presented were carefully selected from a total of 94 submissions. Also included are nine invited papers and two abstracts of invited talks. The papers cover the whole range of theoretical computer science including programming theory, complexity theory, mathematical logic, rewriting, grammars, formal languages, theory of algorithms, computational graph theory, etc.
Keywords: Programming theory, Complexity theory, Mathematical logic, Formal languages, Theory of algorithms, Computational graph theory; Computer science